INOVASI PEMBELAJARAN TEKS MELALUI TEKS PUISI - Wahyuni, Tri; Darni, Darni; Raharjo, Resdianto Permata (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2024)
ABSTRACT Literature learning is a crucial element in character development, aesthetic sensitivity, and the enhancement of critical thinking skills. However, literature learning often tends to be monotonous. The presence of poetry texts is recommended as an innovation in literature teaching. Therefore, this research aims to analyze poetry texts as one of the innovations in literature learning. The methodology applied in this research is descriptive qualitative, with data collection techniques through observation and interviews with teachers and students at the secondary school level. The research shows that the text poetry method is an effective innovation in literature learning that can enhance students' understanding, appreciation, and engagement. Although it faces challenges such as complex preparation and limited time, this method is worthy of development and integration into teaching with appropriate adjustments and technological support. Additionally, this approach encourages students to better understand the structure and meaning of poetry through the integration of personal experiences and socio-cultural contexts. This article recommends the implementation of text-based poetry as part of an innovative literature teaching strategy in schools. ABSTRAK Pembelajaran sastra merupakan elemen krusial dalam pengembangan karakter, kepekaan estetika, dan peningkatan kemampuan berpikir kritis. Namun, pembelajaran sastra sering kali bersifat monoton. Keberadaan puisi teks disarankan sebagai inovasi dalam pengajaran sastra. Oleh karena itu, penelitian ini bertujuan untuk menganalisis teks puisi sebagai salah satu inovasi dalam pembelajaran sastra. Metodologi yang diterapkan dalam penelitian ini adalah deskriptif kualitatif, dengan teknik pengumpulan data melalui observasi dan wawancara dengan guru serta siswa di tingkat sekolah menengah. Penelitian menunjukkan bahwa metode puisi teks merupakan inovasi efektif dalam pembelajaran sastra yang mampu meningkatkan pemahaman, apresiasi, dan keterlibatan siswa. Meskipun menghadapi tantangan seperti persiapan yang kompleks dan keterbatasan waktu, metode ini layak dikembangkan dan diintegrasikan dalam pengajaran dengan penyesuaian serta dukungan teknologi. Selain itu, pendekatan ini mendorong siswa untuk lebih memahami struktur dan makna puisi melalui integrasi pengalaman pribadi dan konteks sosial budaya. Artikel ini merekomendasikan implementasi puisi teks sebagai bagian dari strategi pengajaran sastra yang inovatif di sekolah.